The Effect of ratio of Taro with Tempeh Flour and Concentration of Baking Soda on Taro Crackers Quality - Putra Ginting; Sentosa Ginting; Lasma Nora Limbong (Jurnal Rekayasa Pangan dan Pertanian, 2013)
The Effect of ratio of Taro with Tempeh Flour and Concentration of Baking Soda on Taro Crackers Quality. This study was conducted to determine the effect of taro flour ratio with tempeh flour and baking soda concentration on the quality of taro crackers. The study was performed in October-December 2012 at the Laboratory of Food Technology, Faculty of Agriculture, University of North Sumatra, Medan, using Factorial Completely randomized block design with two factors i.e. ratio of taro with tempeh flour (A) (100%: 0%), (85 %: 15%), (70%: 30%), and (55%: 45%) and baking soda (C) with concentration (0.1%), (0.2%), (0.3%), and (0.4%). Parameters analyzed before frying were water content, ash content, protein content, fat content, and after frying were fat content, organoleptic taste, color and crispness. The results showed that ratio of taro and tempeh flour had a highly significant effect on water content, ash content, protein content, fat content before frying and after frying, organoleptic taste, color and crispness while the baking soda had a highly significant effect on water content, ash content, organoleptic color and crispness and had no significant effect on levels of fat before frying and organoleptic taste. Interactions of ratio tempeh and taro flour and baking soda had no different effect on moisture, ash content, protein content, fat content before and after frying, organoleptic taste, color and crispness. The best crackers way the A2C2 treatment (85% taro and 15% tempeh flour) and 0.2% baking soda. . Key words : baking soda, taro crackers, tempeh flour